Kaposi sarcoma in an HIV-infected patient with high CD4 count: a case report and literature review - Tukeni, Kedir Negesso; Kebede, Merid Lemma; Abadiko, Elias Ababulgu; Woyimo, Tamirat Godebo; Abafogi, Abdo Kedir; Ashine, Amare Hailu; Gudina, Esayas Kebede (Frontiers in Medicine, 2025)
Kaposi sarcoma is a tumor commonly associated with human herpesvirus 8 (HHV-8) infection and is more prevalent in individuals with immunosuppression, such as those with HIV/AIDS, organ transplant recipients, or other conditions causing immune dysfunction. It typically presents as purple patches or nodules commonly affecting the skin or mucous membrane of the gastrointestinal tract, and can spread to the lymph nodes and lungs. This case report describes an 18-year-old male with vertical HIV infection, managed on a regimen of dolutegravir/lamivudine/tenofovir (DTG/3TC/TDF), and with a recent CD4 count of 627cells/mm3and recent viral load of 378 copies/ml, presented with exacerbation of shortness of breath, productive cough with blood-tinged sputum, and a diffuse skin rash. The patient also had tongue swelling with purple discoloration, as well as swelling of the entire left leg and right arm. On physical examination, the patient appeared acutely ill with marked respiratory distress. Notable findings included a bluish, exophytic mass with irregular borders involving the posterior tongue and the hard palate. There was also non-tender, soft, multiple submental and supraclavicular lymphadenopathy, bilateral crackles on lung auscultation, and widespread, patchy, nodular skin lesions. A high-resolution computed tomography (CT) scan of the lungs was suggestive of Kaposi sarcoma that was confirmed with skin biopsy. The patient was treated initially with antibiotics, and supplemental oxygen, while continuing anti-retroviral therapy. The case underlines that though epidemic Kaposi sarcoma is often a disease of immunosuppressed people caused by retroviral infection, there is still the possibility in those with high CD4 counts despite viral load remains low. A high level of suspicion in high-risk patients presenting with characteristic skin lesions is critical for early diagnosis and prompt initiation of available treatment options for a better patient outcome.